Metabolic consequences of perinatal bisphenol A and 17α-Ethinylestradiol exposure manifest in circadian alterations of energy homeostasis in adult male mice - Kalló, Imre; Kádár, Andrea; Göblyös, Barbara; Vastagh, Csaba; Pap, Dániel M.; Fekete, Csaba; Liposits, Zsolt (Frontiers in Endocrinology, 2026)
IntroductionEnvironmental estrogenic chemicals can cross the maternal–fetal barrier and disrupt endocrine and metabolic regulation in the developing embryo/fetus. Bisphenol A (BPA) and 17α-ethinylestradiol (EE2) are widely present in the environment and have been linked to increased cardio-metabolic disease risk.PurposeThis study investigated the effects of maternal BPA and EE2 exposure on metabolic function and circadian energy regulation in male offspring.MethodsPregnant and lactating dams were chronically administered BPA (20 µg/kg bw/day) or EE2 (0.01 µg/kg bw/day) via osmotic minipumps from gestational day 9 to postnatal day 21 to mimic environmental exposure. Adult male offspring (60–80 days old) were assessed for body composition, fasting glucose, and metabolic and activity parameters using the TSE Phenomaster system.ResultsBPA-exposed offspring exhibited reduced lean body mass, fat mass, fat ratio, and 24-hour fasting glucose levels compared to controls and EE2-exposed offspring. Both BPA- and EE2-exposed groups showed altered circadian patterns of locomotor activity, food intake, energy expenditure, and respiratory exchange ratio, with effects predominantly occurring during the night phase.ConclusionsMaternal exposure to environmentally relevant doses of BPA or EE2 can alter the development and function of metabolic regulatory systems, producing distinct disruptions in circadian energy homeostasis in adult offspring. These differential effects likely reflect the partially overlapping yet distinct organizational and activational pathways through which these endocrine-disrupting chemicals act during the perinatal period.